EFFECT OF DEBT FINANCING ON FINANCIAL PERFORMANCE OF LISTED DEPOSIT MONEY BANKS IN NIGERIA - Adedamola Ayinde BAMGBOYE (Malete Journal of Accounting and Finance, 2024)
This study examined the effect of debt financing on financial performance of listed deposit money bank in Nigeria. One of the most important topics in corporate finance is how debt financing affects the financial performance of Nigerian listed deposit money banks. These banks are financial intermediaries, and their stability, profitability, and expansion depend on having a balanced capital structure. Debt financing presents certain risks and expenses associated with financial hardship, interest commitments, and liquidity limits, even though it is advantageous for leveraging profits and optimizing tax shielding. Determining the ideal leverage for these institutions requires an understanding of how debt levels affect performance indicators like return on equity (ROE), return on assets (ROA), and net interest margin. This study adopted ex-post facto research design. Twenty-two deposit money banks made up the of the twenty-two deposit money banks that made up the research population, 13 listed were selected for sampling. Secondary data were utilized, by extracting relevant data from financial statement for a period ranging for a ten years period (2014 – 2023). The findings revealed that debt financing takes a significant effect on debt has high significant effect on ROA (P = 0.000010< 0.05 and ROE (P= 0.002586<.05 on Nigeria listed deposit money banks. The conclusion of the study states that, effect of debt financing on financial performance is significant on listed deposit money banks in Nigeria. It thus recommended that DMBs should focus on optimizing prudent debt financing practices to effectively manage their loan to deposit ratios. Also, banks should strategically use debt to enhance asset utilization and profitability.